Theology of Character Education From the Perspective of The Qur'an In Supporting Islamic Education Curriculum - Muhamad Yusuf; Luqyana Azmiya Putri; Nurul Alamin; Jalwis Jalwis; Eva Ardinal (Sustainable, 2022)
This paper aims to understand the relevance of the education character perspective of the Koran in the shape of generation Qur'anic. The phenomenon found that many students still carry out intolerant actions, brawls, sexual harassment and even acts of radicalism. Character education gets attention and has a strong enough impetus to create a generation of character today. Method research used is study library research. Technique data collection using data reduction, data presentation, and withdrawal conclusion. Results study this show that education character has relevance in the Qur'an. Score education has taken character namely tolerance, religion, love of peace, and love of homeland. Like in QS al - Kafirun: 6 explains suggestion tolerance where the value that can be actualized is by putting forward principle each other value difference, QS Al- Jatsiyah: 22 explains about behaviour religious reflect an awareness that every action will get a reply from God. Surah Al-Anfal: 61 explains to remember God so that one could withhold self from deed zalim and avoid contention. QS Al-Hujurat: 1 3 explains that God created man in diverse, national, and tribal ways that needed unity Among one another. To realize unity, somebody must put forward an attitude of empathy, mutual value and no hostility. With the fourth score character, the Qur'an perspective can become Foundation for shaping the qur'anic generation. The four values ​​of character education are supports that can strengthen the curriculum of Islamic religious education in Indonesia.